Many Great Migrations: Colonial History and the Contest for American Identity. Issue 3 (3rd July 2021) - Rowley, Matthew
Abstract : If we think of the nation as a table, perhaps a Thanksgiving one, who belongs around it? Who is the host, and who the guest? What are the criteria for inclusion, and who gets to decide? This article uses the 400th anniversary of the Mayflower and the "First Thanksgiving" to explore "many great migrations." For those migrating and for those who encounter the migrants, the movement of peoples prompts fundamental questions of identity, difference, inclusion, and belonging. Perhaps looking at history can help those in the present view the challenging questions posed by new peoples as an opportunity.